2021
DOI: 10.1108/inmr-08-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

The role of university environment in promoting entrepreneurial behavior: evidence from heterogeneous regions in Brazil

Abstract: Purpose The purpose of this study is to evaluate the microfoundations of student entrepreneurship, a cornerstone of innovation ecosystems. To this end, this paper assesses how perceived university support for entrepreneurship influences entrepreneurial characteristics and intentions in students enrolled at Amazonas and São Paulo State Universities. Design/methodology/approach A quantitative approach based on multivariate data analysis using confirmatory factor analysis and structural equation modeling was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 57 publications
3
21
1
1
Order By: Relevance
“…First, it contains the bulk of the Brazilian megalopolis, a massive conurbation which provides entrepreneurs with agglomeration economies – such as access to markets, business opportunities and connections with incumbents and support structures (Schaeffer et al , 2021; Fischer et al , 2018). Also, this region comprises most of the leading universities and research institutes in Brazil and has a strong technological activity for the standards of a developing country (Rocha et al , 2021; Alves et al , 2021). Ultimately, this translates into a wealthy knowledge environment that disseminates entrepreneurial capabilities (Fischer et al , 2018).…”
Section: Methodological Approachmentioning
confidence: 99%
“…First, it contains the bulk of the Brazilian megalopolis, a massive conurbation which provides entrepreneurs with agglomeration economies – such as access to markets, business opportunities and connections with incumbents and support structures (Schaeffer et al , 2021; Fischer et al , 2018). Also, this region comprises most of the leading universities and research institutes in Brazil and has a strong technological activity for the standards of a developing country (Rocha et al , 2021; Alves et al , 2021). Ultimately, this translates into a wealthy knowledge environment that disseminates entrepreneurial capabilities (Fischer et al , 2018).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Providing knowledge about entrepreneurship as a career choice and opportunities to participate in running simulated or real business through entrepreneurship education can, therefore, potentially play an important role in developing students' selfefficacy. However, the impact of educational support for entrepreneurship on students' EI remains mixed, with some studies finding a positive relationship (Saeed et al, 2015;Wegner et al, 2020), while others no relationship (Mustafa et al, 2016;Rocha et al, 2021). Secondly, concept development support can help students nurture and develop their business ideas, thus improving their chances of successful commercialisation (Choi et al, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, research has found entrepreneurial climates to foster students’ EI above and beyond their individual-related characteristics (Bergmann et al , 2018). Therefore, it is important to understand the relationships between formal (university support) and informal (entrepreneurial climate) contexts within universities and how they stimulate students’ EI (Rocha et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brazilian institutional context, public universities concentrate most researchers and their technology transfer activities are regulated by government acts (Fischer et al , 2018; Moraes et al , 2021). Despite the recent advance of research carried out in Brazilian private universities, public universities are still classified as the main organizations in research and teaching quality (Rocha et al , 2021). However, the ecosystem of public universities is more developed for scientific research activities than for entrepreneurial activities (Barral et al , 2018; Moraes et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%